Discovering the music of India [videorecording] - Wilets, Bernard (Encyclopedia Britannica Educational Corporation, 1982)
Introduces traditional dance in India as a related art form. Compares that of India's musical forms with those of Western countries, discusses the significance of improvisation in Indian music, and describes the instruments used to create each region's unique musical style.